Formulation and Characterisation of Some Pelleted Feeds for Penaeus monodon - P., Gokulakrishnan; S., Bandyopadhyay (Fishery Technology, 2025)
Three least cost feed formulae were designed with the help of linear programming model on the basis of nutritional and energy requirement of Penaeus monodon and processed through conventional meat mincer and cooking extruder. Four feeds developed from these formulae were characterised with respect to proximate composition, energy, pellet diameter, true and bulk densities, settling rate and water stability. Results showed that these feeds resemble some commercial shrimp feeds available in the market. Aquarium culture experiments with these feeds yielded feed conversion ratio similar to each other, but slightly higher than that of the commercial feed sample.